Intein-mediated thyroid hormone biosensors: towards controlled delivery of hormone therapy - Martí-Baena, Quim; Pascuet-Fontanet, Andreu; Berjaga-Buisan, Tomas; Caravaca-Rodríguez, Miriam; Puig-Costa-Jussà, Jaume; Sanchez-Mejias, Avencia; Ivančić, Dimitrije; Mogas-Díez, Sira; Güell, Marc; Macia, Javier (Frontiers in Systems Biology, 2024)
Although blood sampling and medical imaging are well-established techniques in clinical diagnostics, they often require long post-processing procedures. Fast and simple quantification of signaling molecules can enable efficient health monitoring and improve diagnoses. Thyroid hormones (THs) treatment relies on trial-and-error dose adjustments, and requires constant tracking via blood tests. Thus, a fast and reliable method that can constantly track THs levels could substantially improve patient quality of life by reducing their visits to doctors. Synthetic biosensors have shown to be inexpensive and easy tools for sensing molecules, with their use in healthcare increasing over time. This study describes the construction of an engineered THs bacterial biosensor, consisting of a split-intein-based TH receptor ligand binding domain (LBD) biosensor that reconstitutes green fluorescence protein (GFP) after binding to TH. This biosensor could quantitatively measure THs concentrations by evaluating fluorescence intensity. In vitro sensing using Escherichia coli produced GFP over a wide dynamic range. The biosensor was further optimized by adding a double LBD, which enhanced its dynamic range until it reached healthy physiological conditions. Moreover, a mathematical model was developed to assess the dynamic properties of the biosensor and to provide a basis for the characterization of other intein-mediated biosensors. This type of biosensor can be used as the basis for novel treatments of thyroid diseases and can be adapted to measure the concentrations of other hormones, giving rise to a series of mathematically characterized modular biosensors.